PEMILIHAN PEMASOK BAHAN MENTAH PADA RESTORAN CHANG THIEN HAKKA KITCHEN MENGGUNAKAN METODE AHP DAN TOPSIS - Victor Victor; Dedi Trisnawarman; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
In this globalization era, technology plays a significant role in human’s life. Many systems have been developed to help people work efficiently and to reduce human error. Nowadays, decision making is one of the most important things in companies. Making the right decision may affect company’s profit and success.In this thesis, a research is made to help Chang Thien Hakka Kitchen Restaurant in choosing the best supplier effectively and efficiently. In many restaurants, production process is a very important process in the continuous growth and profitability of the restaurants. The effectiveness and efficiency of production process is determined by many factors such as availability of raw materials, quality of raw materials, price of raw materials, and so on. In this thesis, Chang Thien Hakka Kitchen Restaurant is using 6 criteria in determining the best supplier such as price of raw material, quality of raw material, suppliers’ location, supply management, suppliers’ flexibility, suppliers’ service.Therefore, it is very crucial to choose the best supplier of raw materials for the restaurant.Through this research, it is known that currently Chang Thien Hakka Kitchen Restaurant still chooses its supplier manually. In this thesis, a decision support system for Chang Thien Hakka Kitchen Restaurant is developed using a combination of Analytical Hierarchy Process (AHP) and Technique for Others Performance by Similarity to Ideal Solution (TOPSIS) where the criteria used in evaluating the best supplier is determined by the restaurant management. Then, the qualitative criteria are converted into quantitative data so that it can be measured objectively.At last, the program was tested by user and had the same result with the manual calculation (program error 0,002). Key word supplier, selection, method, AHP, TOPSIS, DSS